Cultural Sense Analysis of Reading Text for the Seventh Grade in the Junior High School English Textbook: â€œEnglish for Nusantaraâ€ - Ramadhani, Zakia; Refnaldi, Refnaldi (Journal of Languages and Language Teaching, 2024)
Cultural sense in English textbooks is essential for fostering cultural sensitivity, developing cross-cultural communication skills, promoting cultural competence, encouraging critical thinking, and enhancing cultural literacy, This research aims to investigate the cultural sense represented in the textbook entitled "English for Nusantara." This research used descriptive qualitative research. The data was analyzed from the content of reading text in a textbook for grade VII junior high school using the Merdeka Belajar curriculum. The research instruments used documentation. The ways to collect the data was cultural sense analysis guidelines. The researcher analyzed the data by reading over all the reading texts in the textbook and continued to analyze more specifically. Second, the researcher was given the codes for each cultural piece of content. Third, the researcher analyzed the text, sentence, or word into cultural content in the text based on theory, and the percentage of the cultural content result was calculated using the percentage formula. The study found 15% of the aesthetic sense, 21% of the sociological sense, 31% of the semantic sense, and 33% of the pragmatic sense. The results show that the highest percentage is the presence of pragmatic sense, while the least is aesthetic sense. The results also show that although the four senses are present, the frequency among the four senses is not balanced. This implies the purpose and emphasis of textbooks in foreign language learning; textbooks emphasize language use more than grammar and structure skills.